Pengaruh Karakteristik Direksi Terhadap Kinerja Perusahaan yang Terdaftar di Bursa Efek Indonesia - Audrey Winona Aprilia; Renita Febriany; Luciana Haryono; Nany Chandra Marsetio (Universitas Kristen Maranatha, 2020)
Directors are human resources who play an important role in maintaining the long-term sustainability of the company's business. Thus, this study aims to determine board size, CEO tenure, and foreign director on company performance in the non-financial industry on the Indonesia Stock Exchange in 2013-2018 with multiple linear regression analysis using 1,764 sample data from 294 companies. Contributions in this study using resource dependency theory, stewardship theory and foreign directors variables as indicators of independence. The results of the study board size have a significant positive effect on company performance, with an optimal number of 4-9 people because it can provide diverse perspectives and ideas in decision making. CEO tenure does not affect ROA and ROE because the president director tends to reject and avoid risks and company's performance is influenced by all directors, not just the president director. Foreign directors have a significant positive effect on ROA with an optimal percentage of 26-50% because they provide different perspectives on decision making, but does not affect ROE with 51-75% of the optimal amount because does not have large influence to influence decisions in improving company performance. Keywords: Director’s Characteristics, Firm Performance, Resource Dependency Theory, Stewardship Theory.